2022
DOI: 10.1002/acr.25020
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Multimorbidity and Comorbidities in Rheumatoid Arthritis

Abstract: Objective To identify differences in multimorbidity and individual comorbidities among individuals with rheumatoid arthritis (RA), separated by race and ethnicity. Methods This case–control study within OptumLabs Data Warehouse from 2010 to 2019 matched RA cases (defined by 2 codes plus prescription of an RA drug) to non‐RA controls 1:1 on age, sex, race and ethnicity, region, index date of RA, and insurance coverage duration. We defined multimorbidity as the presence of ≥2 or ≥5 validated comorbidities. Logis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Thus, the degree of overrepresentation for white patients and underrepresentation for black patients in AS may be all overestimated, as were in PsA 3 . The degree of overestimation may be lower for RA, as a recent study with 154 391 enrollees showed a minor variation in racial/ethnic distribution from the 2020 national data 33 . Epidemiological data related to racial/ethnic distribution in different IAs is minimal.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, the degree of overrepresentation for white patients and underrepresentation for black patients in AS may be all overestimated, as were in PsA 3 . The degree of overestimation may be lower for RA, as a recent study with 154 391 enrollees showed a minor variation in racial/ethnic distribution from the 2020 national data 33 . Epidemiological data related to racial/ethnic distribution in different IAs is minimal.…”
Section: Discussionmentioning
confidence: 98%
“…3 The degree of overestimation may be lower for RA, as a recent study with 154 391 enrollees showed a minor variation in racial/ethnic distribution from the 2020 national data. 33 Epidemiological data related to racial/ethnic distribution in different IAs is minimal. More relevant high-quality studies should be conducted to provide a better reference source for clinical trial patients' involvement.…”
Section: Discussionmentioning
confidence: 99%